Influence of Injection Pressure and Aluminium Oxide Nano Particle-Added Fish Oil Methyl Ester on the Performance and Emission of Compression Ignition Engine - K. M. Akkoli; S. C. Kamate; S. N. Topannavar; A. R. Bhavimani; N. R. Banapurmath; Ibham Veza; Manzoore Elahi M. Soudagar; T. M. Yunus Khan; A. S. El-Shafay; M. A. Kalam; M. M. Shivashimpi; Archana M. Gulli (Energies, 2022)
The present experimental examination was carried out to suggest a better fuel blend with an optimised dosage level of alumina nanoparticles (Al2O3)—in a mixture of Fish Oil Methyl Ester (FOME) biodiesel and diesel—and injection pressure, wherein enhanced performance and reduced emissions were obtained via a diesel engine. The aluminium nanoparticles were added to the mixture in 5 mg/l steps through varying concentrations from 5 to 20 mg/L. The experimental results showed that engine performance quietly reduces with increased emission characteristics with the addition of raw FOME biodiesel compared to diesel. Furthermore, the addition of aluminium nanoparticles (Al2O3) improved the performance as well as the emission characteristics of the engine. Among all the test blends, the B40D60A20 blend provided a maximum brake thermal efficiency of 30.7%, which is 15.63% superior to raw FOME and 3.90% inferior to diesel fuel. The blend also showed reduced emissions, for instance, a reduction of 48.38% in CO, 17.51% in HC, 16.52% in NOx, and 20.89% in smoke compared to diesel fuel. Lastly, it was concluded that B40D60A20 at 260 bar is the optimised fuel blend, and 20 mg/l is the recommended dose level of aluminium nanoparticles (Al2O3) in the FOME–diesel mixture biodiesels in order to enhance the performance and emission parameters of a diesel engine.